Q-switched erbium-doped fibre laser based on molybdenum disulfide and tungsten disulfide as saturable absorbers - Mohamed, K.H.; Hamida, Belal Ahmed; Khan, Sheroz; Hussein, L.A.; Ahmat, M.O.; Ismail, Ezzatul Irradah; Kadir, N.A.A.; Latif, Amirah Abdul; Harun, Sulaiman Wadi (Institute of Physical Optics, 2017)
A passively Q-switched erbium-doped fibre laser is experimentally implemented, using molybdenum disulfide (MoS2) and tungsten disulfide (WS2) as saturable absorbers. The results testify that a WS2-based Q-switched fibre laser generates more stable pulse trains, if compared with the MoS2-based saturable absorber. The wavelength region where the Q-switched pulses have been obtained is a so-called C-band region. The central wavelengths are 1559 and 1560 nm for MoS2 and WS2, respectively.